The Role of Teacher’s Feedback on Students’ English Language Learning Outcomes at College of Nursing Bhakkar: Descriptive Cross-Sectional Study: Teacher’s Feedback Impact and Students’ Learning Outcomes - Bibi, Sumayya; Khurshid, Saba; Parveen, Shagufta; Parveen, Zareena; Dildar, Umbreen (Pakistan Journal of Health Sciences, 2024)
Feedback in English language learning can help teachers to provide more meaningful feedback that can help students to achieve their learning objectives. Therefore, the study was carried out to examine the role of teacher feedback on students’ English language learning outcomes. Objective: To assess the role of teacher feedback on nursing students’ English Language learning outcomes at the College of Nursing, Bhakkar, Pakistan. Methods: A cross-sectional study designed to achieve the aims of the study. Duration of study was from January 2024 till March 2024. A total of undergraduate nursing students 150 samples were recruited from Nursing College, Bhakkar using a universal sampling technique. Data were collected with the help of an adapted questionnaire which consisted of two sections. In one section 7 items were related to teacher feedback and 8 items were related to student learning outcome. SPSS version 24.0 was used for data entry and data analysis. Descriptive and inferential statistics were applied to study variables. Results: The study results showed a significant positive role of teacher feedback on nursing student English language learning outcomes. 84.7% of participants strongly agreed that it is beneficial for teachers to underline their mistakes. Similarly, 80.7% acknowledged that teacher feedback aided in their comprehension of their strengths and weaknesses in English Conclusions: Teacher feedback is imperative for academic success and professional development. Teacher feedback great impact on nursing students’ English language learning.